Gender differences in time allocation contribute to differences in developmental outcomes in children and adolescents - Ha Trong Nguyen; Sally Brinkman; Huong Thu Le; Stephen R. Zubrick; Francis Mitrou (Global Labor Organization (GLO), 2022)
Using over 50 thousand time-use diaries from two cohorts of children, we document significant gender differences in time allocation in the first 16 years in life. Relative to males, females spend more time on personal care, chores and educational activities and less time on physical and media related activities. These gender gaps in time allocation appear at very young ages and widen overtime. We provide novel evidence that gender differentials in time investment are quantitatively important in explaining a female advantage in most cognitive and non-cognitive skills. Moreover, gender disparity in educational time outside of school is the most important factor contributing to gender test score gaps and its contribution is more pronounced for higher performing students. By contrast, gender differences in media time are the main factor explaining gender gaps in non-cognitive skills. As children age, gender differences in time allocation play an increasing role in explaining gender gaps in both cognitive and non-cognitive skills.
Keywords: I24; J13; J16; J22; J24; 330; Time Allocation; Time Use Diary; Gender Gap; Human Capital; Child Development